Mengganti Mikrokontroller Mesin Dust Collector pada PT. xxx dengan PLC OMRON CP1E-NA20CD-R - Surawan Setiyadi; Edo Aulia Billy Fany (Journal of Electrical And Electronics Engineering, 2021)
As a result of the production of powder processing causes a lot of dust around the production machine and factory. This of course can cause pollution. Dust needs to be collected using a Dust Collector (DC) machine. The controller on the DC machine at PT. xxx is often damaged in the control unit and requires repairs at a cost of around Rp. 5,000,000 per unit. In facts there are about 10 units of machines at PT.xxx that must work all. Because of DC machines are often damaged in their controllers, the maintenance department made a development to make replacement DC machine controllers. Namely using the Programmable Logic Controller (PLC). This PLC replaces the microcontroller unit on the DC machine, PLC uses ladder diagram programming language that is easily understood by some people working in the world of control. PLC parts that are easily found in the market and programming languages that are easy to understand and reliability make one of the reasons this PLC is used to replace the microcontroller unit.